Contemporaneous and Lagged 𝑅² Decomposed Connectedness: Evidence for Stock Market Indices, Thematic ETFs, Bitcoin, Brent Crude Oil and Geopolitical Risks - Fekria Belhouichet; Guglielmo Maria Caporale; Luis Alberiko Gil-Alana (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper applies the R² connectedness method proposed by Balli et al. (2023) to analyse contemporaneous and lagged connectedness between returns on several asset classes (sector ETFs, Bitcoin, stock market indices, Brent crude oil) over the period 1 January 2023 – 22 September 2025, in the presence of heightened geopolitical risk. The results indicate that contemporaneous effects dominate over lagged ones. Specifically, the Nikkei 225, the STOXX 600, and Brent oil act as net risk receivers, while Bitcoin plays a limited role as a safe haven. Conversely, the S&P 500 index appears to be the main shock emitter, followed by the Defence (ITA) and Technology (XLK) ETFs, while the Energy (XLE) ETF seems to be particularly exposed to risk. These findings provide valuable information to policymakers responsible for financial stability and to investors seeking effective portfolio diversification and hedging strategies, especially during periods of market turbulence.
Keywords: C32; G11; 330; contemporaneous and lagged 𝑅² connectedness; Thematic ETFs; Brent oil; S&P 500; STOXX 600; Nikkei 225; geopolitical risk